Knee performance and self-efficacy trajectory curves after ACL reconstruction: A longitudinal study. (May 2021) - Pua, Yong-Hao; Low, Juanita; Woon, Ee-Lin; Tay, Olivia Shi-Min; Cheong, Philip; Thumboo, Julian; Clark, Ross Allan; Chang, Paul; Tan, Andrew; Ho, Jia-Ying
Abstract: Objectives: To examine knee flexion range-of-motion, quadriceps strength, and knee self-efficacy trajectory curves over 6 months after anterior cruciate ligament reconstruction (ACLR), stratified by patients' Month-6 sports activity level. Design: Prospective longitudinal study. Setting: Hospital outpatient physiotherapy department. Participants: 595 individuals after unilateral ACLR (mean age, 27 years). Main outcome measures: At 2-, 3-, and 6-months post-surgery, knee flexion range-of-motion, quadriceps strength, and self-efficacy were quantified. Flexion range-of-motion was additionally measured at 2- and 4-weeks post-surgery. Sports activity levels were assessed using the Tegner Activity Score at 6-months post ACLR. Results: The various measures improved nonlinearly over time, with substantial improvements observed in the first 2–4 months post-surgery. In multivariable generalized least squares models, greater knee flexion range-of-motion, quadriceps strength, and self-efficacy over time were significantly associated with higher Month-6 Tegner levels (all P values < 0.01). Additionally, receiving a bone-patellar-tendon-bone graft or meniscal repair was associated with lower quadriceps strength trajectories ( P -values<0.001) while female sex was associated with lower knee self-efficacy trajectories ( P  = 0.02). Conclusions: Greater knee flexion range-of-motion, quadriceps strength, and self-efficacy were associated with higher Month-6 Tegner levels. The derived trajectory curves may be useful for effective management decision making and adequate results interpretation during the rehabilitation process. Highlights: Higher knee flexion ROM, knee strength, and self-efficacy trajectories were associated with higher Month-6 Tegner levels. Receiving a bone-patellar-tendon-bone graft or meniscal repair was associated with lower quadriceps strength trajectories. Female sex was associated with lower knee self-efficacy trajectories. An interactive website was created (https://sghpt.shinyapps.io/alpha/ ) where the trajectory curves can be explored in detail.